Peran Pendidikan Dalam Mendukung Sustainable Develompent Goals (SDGs) - Fitriyah, Ayda; Nugraheni, Nursiwi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Currently, the world is experiencing complex and dynamic developments, with its problems. People around us are often faced with social and economic challenges such as conflict, social inequality and poverty. Education for sustainable development is expected to produce a generation that has a sustainable mindset. Currently, Indonesia is trying to improve the quality of its education through implementing the "Merdeka Belajar" curriculum. It is hoped that this step will be a great opportunity for Indonesia to improve the quality of education and increase its competitiveness when compared to other countries. The aim of writing this article is to analyse the role of education in supporting sustainable development. This writing is descriptive and uses various relevant literary sources such as scientific journals. This writing uses data collection techniques or literature studies which are based on information presented in previous research. This article discusses the very important role of education in sustainable development, both domestically and at the global level. Apart from providing knowledge and skills, education also shapes character, increases social, environmental and economic awareness, and teaches individuals responsibility. Programs such as SATAP, SM3T, and Calistung play a major role in supporting quality education and sustainable development.